Supplier-Customer collaboration: A Chinese 4PL case - Xu, Haolu (2008)
As global competition is becoming an ever growing business reality, competition does not take place among individual businesses anymore but between their supply chains where collaboration has been a predominant factor in determining their success. This dissertation presents a case study in the topic of customer supplier collaboration from a unique point of view the one of a Chinese 4PL business dealing with both European and Chinese customers. The dissertation reveals collaboration being used as an asset by the company as a mean to satisfy their customer requirements and build competitive advantage and how customer's expectations and requirements provide a driving force for it to happen. The dissertation also explores the reality of differing collaboration requirements between a Chinese and a European customer.